Efficiency Improving Methodology for Corporate Social Responsibility Indicators in Order to Ensure the Energy Transition Using Information Modeling Tools - KODANEVA, SVETLANA I. (The journal of contemporary issues in business and government, 2021)
The current state of the environment and the emerging economic trends, especially in the energy sector, have created serious preconditions for an accelerated energy transition. This requires extractive companies to restructure their business models by increasingly introducing criteria for assessing corporate social responsibility. However, this is hindered by the lack of uniform standards for their calculation, which can lead to manipulation in investment markets. This study is devoted to an urgent problem, i.e. the methodology development for increasing the efficiency of the indicators of corporate social responsibility based on the information modeling. The technology, traditionally used in technological industries, in construction, in particular, has not yet been considered as a comprehensive methodology for organizing investment processes and making investment decisions. In the study course, a hypothesis about the effectiveness of information modeling as a methodological and instrumental basis for assessing corporate social responsibility was put forward and tested. The author has developed their model for creating a unified information platform for making investment decisions in the fuel and energy complex.